The Strategic Role of Digital Transformation: Leveraging Digital Leadership to Enhance Employee Performance and Organizational Commitment in the Digital Era - Guanming Qiao; Yannan Li; Ahreum Hong (Systems)
Given the rapid advancements in the digital transformation era, digital leadership has become essential for enhancing employee performance and organizational commitment. This study specifically examines the mediating role of digital transformation in the relationship between digital leadership, employee performance, and organizational commitment, drawing on data collected between June and August 2024 from 579 participants across diverse industries. The findings demonstrate that digital leadership significantly enhances employee outcomes by driving digital transformation, which serves as a crucial intermediary that amplifies the positive effects of leadership. This research underscores the importance of aligning leadership strategies with digital transformation initiatives, especially in the DT-driven business landscape, to promote sustainable growth and maintain a competitive edge. By highlighting the combined influence of leadership and digital transformation on employee performance and organizational commitment, this study provides valuable insights for organizations addressing the complexities of digital change. It also emphasizes the pivotal role of leadership in fostering innovation and organizational resilience in the digital transformation era.